Motor Synchronization to Rhythmic Auditory Stimulation (RAS) Attenuates Dopaminergic Responses in Ventral Striatum in Young Healthy Adults: [11C]-(+)-PHNO PET Study - Koshimori, Yuko; Strafella, Antonio P.; Valli, Mikaeel; Sharma, Vivek; Cho, Sang-soo; Houle, Sylvain; Thaut, Michael H. (Frontiers in Neuroscience, 2019)
Auditory-motor entrainment using rhythmic auditory stimulation (RAS) has been shown to improve motor control in healthy persons and persons with neurologic motor disorders such as Parkinson’s disease and stroke. Neuroimaging studies have shown the modulation of corticostriatal activity in response to RAS. However, the underlying neurochemical mechanisms for auditory-motor entrainment are unknown. The current study aimed to investigate RAS-induced dopamine (DA) responses in basal ganglia (BG) during finger tapping tasks combined with [11C]-(+)-PHNO-PET in eight right-handed young healthy participants. Each participant underwent two PET scans with and without RAS. Binding potential relative to the non-displaceable compartment (BPND) values were derived using the simplified reference tissue method. The task performance was measured using absolute tapping period error and its standard deviation. We found that the presence of RAS significantly improved the task performance compared to the absence of RAS, demonstrated by reductions in the absolute tapping period error (p = 0.007) and its variability (p = 0.006). We also found that (1) the presence of RAS reduced the BG BPND variability (p = 0.013) and (2) the absence of RAS resulted in a greater DA response in the left ventral striatum (VS) compared to the presence of RAS (p = 0.003), These suggest that the absence of external cueing may require more DA response in the left VS associated with more motivational and sustained attentional efforts to perform the task. Additionally, we demonstrated significant age effects on D2/3 R availability in BG: increasing age was associated with reduced D2/3 R availability in the left putamen without RAS (p = 0.026) as well as in the right VS with RAS (p = 0.02). This is the first study to demonstrate the relationships among RAS, DA response/D2/3 R availability, motor responses and age, providing the groundwork for future studies to explore mechanisms for auditory-motor entrainment in healthy elderly and patients with dopamine-based movement disorders.